2009
DOI: 10.1002/rcm.4185
|View full text |Cite
|
Sign up to set email alerts
|

Targeted analysis of protein citrullination using chemical modification and tandem mass spectrometry

Abstract: Protein citrullination originates from enzymatic deimination of polypeptide-bound arginine and is involved in various biological processes during health and disease. However, tools required for a detailed and targeted proteomic analysis of citrullinated proteins in situ, including their citrullination sites, are limited. A widely used technique for detection of citrullinated proteins relies on antibody staining after specific derivatization of citrulline residues by 2,3-butanedione and antipyrine. We have rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
56
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(58 citation statements)
references
References 43 publications
2
56
0
Order By: Relevance
“…Phenylglyoxal-rhodamine Probe-Another method that was recently described to be applicable for the detection of citrullinated proteins is based on the chemical reaction of the ureido group of citrulline with phenylglyoxal (36,37). Phenylglyoxal has been reported to react specifically with arginine residues under neutral or basic conditions and with citrulline residues under highly acidic conditions.…”
Section: Methods For the Detection Of Citrullinated Proteins On Westementioning
confidence: 99%
See 1 more Smart Citation
“…Phenylglyoxal-rhodamine Probe-Another method that was recently described to be applicable for the detection of citrullinated proteins is based on the chemical reaction of the ureido group of citrulline with phenylglyoxal (36,37). Phenylglyoxal has been reported to react specifically with arginine residues under neutral or basic conditions and with citrulline residues under highly acidic conditions.…”
Section: Methods For the Detection Of Citrullinated Proteins On Westementioning
confidence: 99%
“…However, this approach did not allow the identification of the site of citrullination. They optimized the procedure further and subjected the chemically modified citrullinated peptides to LC-MS/MS with alternating CID and ETD (36). In this way, citrullinated peptides were detected in the CID spectrum, which showed a dominant peak with an m/z value of 201.1, corresponding to a specific modification-derived fragment ion, and the exact site of citrullination could be determined from the ETD spectrum.…”
Section: Direct Ms Analysis Of Citrullinated Proteins-mentioning
confidence: 99%
“…This modification is catalyzed by peptidylarginine deiminases (PADs) [59], and is often related to gene silencing, since it antagonizes arginine methylation [60]. From an analytical perspective chemical tags such as 18 O, 2,3-butanedione, or antipyrine are useful to convert protein citrullination sites into derivatives for efficient and robust MS detection [61,62], since the mass increment of deimination (+0.984 Da) is rather small and may be obscured by isotope splitting of the peptide signals in MS and MS/MS.…”
Section: Citrullinationmentioning
confidence: 99%
“…12 Diacetyl is used to react with protein-bound arginine to produce protein-bound citrulline. 13,14 Researchers have treated citrullinated residues with diacetyl and antipyrine to create citrullinated proteins which react with anti-cyclic citrulline protein antibodies (ACPAs). 13,15 Recently several authors have suggested that ACPA production accompanies or contributes to…”
Section: Diacetyl and Formation Of Citrulline Antigens: A Hapten Modementioning
confidence: 99%